2015
DOI: 10.1002/pts.2176
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Truck Transport Vibration Levels in China as a Function of Road Conditions, Truck Speed and Load Level

Abstract: Transport vibration levels in trucks were measured as a function of truck speed, road conditions and load level. The trucks consisted of one normally loaded truck and one overloaded truck with leaf-spring suspensions. Truck speeds were divided into three groups: 0-30 km/h, 31-60 km/h and 61-90 km/h. Traffic roads consisted of highways, arterial roads (ARs), secondary roads (SRs) and tertiary roads (TRs). The results revealed that transport vibration levels increased with truck speed; TRs contributed to the hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
40
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(45 citation statements)
references
References 21 publications
5
40
0
Order By: Relevance
“…On the other hand, it has been reported that overloading probably suppresses transport vibration levels, specially at low speeds, what can be seen by the comparison of Figures 5 and 6. Regarding road conditions, higher vibration levels have been detected on rough road surfaces, and these levels are even more significant at high speeds than at low speeds [23].…”
Section: Vibrationmentioning
confidence: 98%
See 1 more Smart Citation
“…On the other hand, it has been reported that overloading probably suppresses transport vibration levels, specially at low speeds, what can be seen by the comparison of Figures 5 and 6. Regarding road conditions, higher vibration levels have been detected on rough road surfaces, and these levels are even more significant at high speeds than at low speeds [23].…”
Section: Vibrationmentioning
confidence: 98%
“…Also, characteristics of the vehicle, such as truck size, truck suspensions, number of axels and gross weight, are important parameters [20,22,23].…”
Section: Parameters In Transportationmentioning
confidence: 99%
“…For having an idea of the effect of loads on vibrations, a recent experiment compared measures provided by two trucks, similar in all technical characteristics, but differently loaded [21]: with 60% and 150% of their maximum truckload. Data are displayed in figure 2 and showed a significant reduction in peaks of acceleration (G) in the case of the overloaded truck.…”
Section: Detecting Vibrations On Truckmentioning
confidence: 99%
“…This preliminary study on techniques and experiences for measuring the mechanical and climatic conditions encountered by palletized products in handling and transport is realized as part of a larger investigation to be performed inside the "MAAS - Truck 11,12,13,14,15,18,19,20,21,22,23,2 4,25,26,30,35,49,53,59 14, 15 23,24,25,26, 29,30 47 56,60,61,62 55,54,47 …”
Section: Acknowledgementmentioning
confidence: 99%
“…With this unavoidable diversity in cargo, LTL carriers are faced with the challenge of optimizing the available space in the trailers with the largest number of shipping units that can be shipped without causing damage and compromising safety. Past research has studied the severity of both physical and climatic levels of various transportation systems and monitored packages in North America, South America, Europe and Asia, including inter-continental shipments [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26]. Based on such studies, organizations like the American Society of Testing and Materials (ASTM), International Safe Transit Association (ISTA), and International Standards Organization (ISO) have developed test methods to perform pre-shipment testing to simulate package testing to various elements that may include atmospheric and climatic conditioning, tip-over, shock and Developing optimum protective packaging to overcome the physical and ambient environment related distribution elements faced by the product-package systems requires a balance between insufficient and excessive packaging.…”
Section: Introductionmentioning
confidence: 99%